Zebrafish Vestigial Like Family Member 4b Is Required for Valvulogenesis Through Sequestration of Transcription Factor Myocyte Enhancer Factor 2c - Xue, Chang; Liu, Xiaohui; Wen, Bin; Yang, Ruimeng; Gao, Shuo; Tao, Jiong; Zhou, Jun (Frontiers in Cell and Developmental Biology, 2019)
A variety of cardiac transcription factors/cofactors, signaling pathways, and downstream structural genes integrate to form the regulatory hierarchies to ensure proper cardiogenesis in vertebrate. Major interaction proteins of the transcription cofactor vestigial like family member 4 (VGLL4) include myocyte enhancer factor 2 (MEF2) and TEA domain transcription factors (TEAD), both of which play important roles in embryonic cardiac development and in adulthood. In this study, we identified that the deficiency of zebrafish vgll4b paralog, a unique family member expressed in developing heart, led to an impaired valve development. Mechanistically, in vgll4b mutant embryos the disruption of Vgll4b-Mef2c complex, rather than that of Vgll4b-Tead complex, resulted in an aberrant expression of krüppel-like factor 2a (klf2a) in endocardium. Such misexpression of klf2a eventually evoked the valvulogenesis defects. Our findings suggest that zebrafish Vgll4b plays an important role in modulating the transcription activity of Mef2c on klf2a during valve development in a blood-flow-independent manner.